ATG7 regulates hepatic Akt phosphorylation through the c‐JUN/PTEN pathway in high fat diet‐induced metabolic disorder. Issue 12 (23rd October 2019) - Zhao, Daina; Zhang, Shuangxi; Wang, Xueqiang; Gao, Dan; Liu, Jing; Cao, Ke; Chen, Lei; Liu, Run; Liu, Jiankang; Long, Jiangang
Abstract : Growing evidence has suggested that autophagy‐related protein 7 (ATG7) plays an important role in insulin signaling, but the mechanism of ATG7 in hepatic insulin sensitivity is not fully understood. The purpose of the present study is to clarify the underlying molecular mechanisms of ATG7 in obesity development. Serum and liver samples from mice fed a high fat diet (HFD) were evaluated for metabolic profile data and ATG expressions during obesity development. We found that compared with other ATGs, ATG7 expression increased earlier with lower hepatic insulin sensitivity in the 4‐wk HFD‐fed mice. For in vitro analyses, silencing ATG7 significantly up‐regulated insulin‐stimulated phosphorylation of protein kinase B (Akt) and down‐regulated phosphatase and tension homolog deleted on chromosome ten (PTEN) in HepG2 cells. Replenishing PTEN to ATG7‐silenced hepatocytes restored the phosphorylated Akt level. Furthermore, ATG7 silencing led to higher c‐JUN expression, which transcriptionally reduced PTEN expression. These results reveal a novel mechanism by which ATG7 regulates Akt phosphorylation via the c‐JUN/PTEN pathway at the early stage of HFD‐induced metabolic disorder.—Zhao, D., Zhang, S., Wang, X., Gao, D., Liu, J., Cao, K., Chen, L., Liu, R., Liu, J., Long, J. ATG7 regulates hepatic Akt phosphorylation through the c‐JUN/PTEN pathway in high fat diet‐induced metabolic disorder. FASEB J. 33, 14296‐14306 (2019). www.fasebj.org